Sedges : Carex - Mohlenbrock, Robert H., 1931- (Illustrated flora of Illinois., 2011)
Sedges: Carex is the fourteenth volume of the Illustrated Flora of Illinois series and the sixth and last volume devoted to monocots-plants that have a single seed leaf, or cotyledon, upon germination. Since the volume's original publication in 1999, thirty-four additional species of plants have been recognized in Illinois. Some are discoveries from recent field work, some are from more thorough searches of herbaria, and others are from different taxonomic philosophies. For each species of Carex in Illinois, there is a full illustration showing the habit of the p.